Liberal land reform in Kazakhstan? The effect on land rental and credit markets - Vasyl Kvartiuk; Martin Petrick (World Development, 2021)
This study analyses the effect of Kazakhstan's 2003–2005 agricultural land reform on land rental and credit market participation. Although the reform declared an intention to facilitate efficient land allocation, we observe a major land concentration. We analyze whether new land relations stimulated land sales and rental markets and made credit more accessible. Utilizing data from two independent surveys before and after private land ownership was introduced, we demonstrate that the reform did not affect the land sales market but reorganized the land-rental market in a top-down fashion with the state remaining the principal landlord. The reform did not achieve the goal of providing access to land for the more skilled producers and did little to facilitate the use of owned land as collateral. The reform achievements are modest and bolder steps will be necessary to improve the functioning of Kazakhstan's agricultural land markets.
Keywords: 330; land rental market; credit market; land reforms; allocative efficiency; Kazakhstan